Assessing Housing Preferences and Living Conditions of Migrant Workers in the Fringe Areas of Bengaluru City, India - Jayprakash Chadchan; Nabil Hossiney; Praveen Kumar Tamil Selvan; Anagha Vijayan (Societies)
This study investigates the housing preferences and its impact on living conditions of migrant industrial workers in the fringe areas of Bengaluru, India, where rapid urbanization and economic expansion have led to a significant demand for affordable housing. Using the Analytic Hierarchy Process (AHP), a multi-criteria decision-making framework, this study analyzed key factors influencing housing choices, such as proximity to the workplace, affordability, and access to essential amenities. Data were collected from 400 respondents through a combination of surveys, complimented by field observations and expert consultations. The findings indicate a strong preference for affordable housing close to employment hubs, with “proximity to workplace” emerging as the most critical criterion with a priority weight of 43.36%, followed by “affordability” with a priority weight of 12.47%. However, field insights reveal a trade-off with housing quality and living conditions. Many migrant workers are confined to overcrowded and poorly ventilated rental units, often provided by employers, which compromises their health and well-being. Our results contribute to the understanding of urban housing challenges in rapidly growing economies and emphasize the importance of sustainable, health-oriented housing policies that can mitigate environmental impacts and improve the quality of life for low-income migrant populations.